Exceptions and Limitations Regime To Copyright - Barrenechea, Alejo (2017)
The exceptions and limitations to authors’ rights is an important part of the regulation on the subject. In this sense, they play a significant role in attenuating the tension between creators and the public that seeks the widest access to the work. Proof of its relevance is the celebration of the Treaty of Marrakesh, where the first time a rule of international law occupies its text in an exclusive way to say matter. However its recognition and the scope of regulation, both nationally and internationally, the difficulties presented are the particularities that the new technological environment involves.